REPRESENTASI KEKUASAAN TINDAK TUTUR DIREKTIF GURU KELAS PADA MADRASAH IBTIDAIYAH ISTIQLAL BANJARMASIN (REPRESENTATION OF THE POWER OF DIRECTIVE SPEECH ACTS PRODUCED BY THE CLASS TEACHER AT MADRASAH IBTIDAIYAH ISTIQLAL BANJARMASIN) - Maulina Maulina (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
Representation of the Power of Directive Acts Produced by the Class Teacher at Madrasah Ibtidaiyah Istiqlal Banjarmasin. This study aims to determine the representation of the teacher’s power in directive speech acts, namely: requests, questions, commands, prohibitions, granting of permission, and advice to classroom teacher and their effects on the students of MI Istiqlal Banjarmasin. This study used a descriptive qualitative approach. This research data were in the form of teacher’s speech acts containing the representation of power during the learning and teaching process. The source of this research data was a classroom teacher who was teaching in the classroom at MI Istiqlal Banjarmasin. The researcher used the pragmatic approach, the listening and the recording techniques to obtain information in accordance with the object to be the focus of the research. The research found six types of representation of the power of directive speech acts made by the classroom teacher in at MI Istiqlal Banjarmasin such as requests, questions, orders, prohibitions, granting permission, and advice. Representation of teacher power in directive speech acts were in the forms of teacher’s expertise, humanity and legitimate power; power in expressing pleasure and displeasure; and power in giving direction and affirmation. The teacher most on often spoke speech acts of questions and commands during the learning and teaching process in the classrom.Keywords: representation, power, teacher, directive speech acts, ibtidaiyah madrasaRepresentasi Kekuasaan Tindak Tutur Direktif Guru Kelas pada Madrasah Ibtidaiyah Istiqlal Banjarmasin. Penelitian ini bertujuan mengetahui representasi kekuasaan dalam tindak tutur direktif permintaan, pertanyaan, perintah, larangan, pemberian izin, dan nasihat pada guru kelas dan efeknya terhadap siswa MI Istiqlal Banjarmasin. Penelitian ini menggunakan pendekatan kualitatif yang bersifat deskriptif. Data penelitian ini berupa tuturan guru saat proses pembelajaran yang tuturannya mengandung representasi kekuasaan.  Sumber data penelitian ini adalah guru kelas di MI Istiqlal Banjarmasin yang sedang mengajar di dalam kelas. Penulis menggunakan ancangan pragmatik, teknik simak dan teknik catat untuk memperoleh keterangan sesuai dengan objek yang menjadi fokus kajian dalam penelitian ini. Hasil penelitian ini ditemukannya enam representasi kekuasaan tindak tutur direktif guru kelas pada MI Istiqlal Banjarmasin seperti permintaan, pertanyaan, perintah, larangan, pemberian izin, dan nasihat. Representasi kekuasaan guru dalam tindak tutur direktif ini berupa kekuasaan kepakaran, humanis, dan absah guru; kekuasaan menyatakan rasa senang dan tidak senang; dan kekuasaan dalam memberi pengarahan dan penegasan. Tindak tutur pertanyaan dan perintah paling sering diujarkan guru saat proses pembelajaran di kelas.Kata-kata Kunci: representasi, kekuasaan, guru, tindak tutur direktif, madrasah ibtidaiyah